Digitalization of the Financial Activities of Platform Companies: Competitive Potential and social Impact - V. P. Bauer; V. V. Eremin; M. V. Ryzhkova (Финансы: теория и практика, 2021)
The aim of the article is to define the characteristics of platform companies and their digital platforms as new mechanisms of competition and social transformation in the global economy. The relevance of the article is due to the demand for theexperience of foreign platform companies as the main business models for the competitive development of the economy. The authors apply methods such as theoretical analysis of scientific publications (analysis, synthesis, generalization); deduction as a procedure for the transition from the general to the particular; analysis of the structure of the influence of platform companies on the strategies of competition, highlighting the differences between the platform and linear business models; determining the influence of platform companies on competition among offline partners; identification of competition between platform companies and within them; highlighting aspects of the social impact of the functioning of platforms and platform companies. The study is based on the works of domestic and foreign authors devoted to the analysis of the development of platform companies and the assessment of the social impact of these processes, as well as the interaction between the authors and developers of digital platforms. The scientific novelty of the article is provided by the analysis of a wide range of competition tools, which favorably distinguish the platform approach to modern business from the linear one. The results of the analysis make it possible to form a model of the competition ecosystem in the platform economy. The authors conclude that the basis of the competitive success of platform companies is their ability to expand the scale of activities (as a result of optimizing various types of assets), to minimize costs by involving external users in the process of creating added value, and cross-platform cooperation. The authors recommend that Russian business entities use the experience of foreign platform companies to gain competitive advantages not only in the Russian IT sector but also outside of it. Particularly important are: decentralization of quality control procedures, creation of new sales markets, collection, and processing of large amounts of data, development of strategies for entering markets as suppliers and contractors, diversification of activities at the stage of attracting investments, a social construction.